ISLAMIC FINANCIAL LITERACY EDUCATION: STUDY OF AL-GHAZALI'S THOUGHT - Faizah, Ima; Rini, Dina Dwi Oktavia; Farihah , Anis (International Journal Multidisciplinary (IJMI), 2024)
Islamic financial literacy is a skill that must be possessed by all levels of society in the midst of developments in this era that offer a variety of products that attract consumer interest. Islam as a comprehensive religion has built character values in terms of Islamic financial literacy. Imam Al-Ghazali, as one of the figures in Islamic education, expressed thoughts about the content of Islamic financial literacy in his works. This article aims to examine Imam Al-Ghazali's thoughts regarding the concept of Islamic financial literacy education including material content and educational methods. The research uses a descriptive qualitative approach with literature study. The results of the research show that the content of Imam Al-Ghazali's Islamic financial literacy education emphasizes the formation of character who obeys the commands of Allah SWT through controlling one's desires. This character includes awareness of the purpose of Allah SWT in providing wealth for humans, paying attention to the principle of halal wealth, using wealth according to needs, not just lustful desires, and spending wealth simply. Islamic financial literacy can be instilled in students through the ibroh method or learning from past experience, example, storytelling and habituation.